2010
DOI: 10.1137/080735850
|View full text |Cite
|
Sign up to set email alerts
|

Hardness-Randomness Tradeoffs for Bounded Depth Arithmetic Circuits

Abstract: In this paper we show that lower bounds for bounded depth arithmetic circuits imply derandomization of polynomial identity testing for bounded depth arithmetic circuits. More formally, if there exists an explicit polynomial f that cannot be computed by a depth d arithmetic circuit of small size, then there exists an efficient deterministic black-box algorithm to test whether a given depth d−5 circuit that computes a polynomial of relatively small individual degrees is identically zero or not. In particular, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(124 citation statements)
references
References 35 publications
2
122
0
Order By: Relevance
“…In [KI04] Kabanets and Impagliazzo proved that PIT can be derandomized if and only if NEXP does not have small arithmetic circuits. Later, [DSY09] observed a similar result for bounded depth circuits. By combining their result with our Observation 1 we obtain the following corollary.…”
Section: Extensions Of Theorem 11supporting
confidence: 61%
See 2 more Smart Citations
“…In [KI04] Kabanets and Impagliazzo proved that PIT can be derandomized if and only if NEXP does not have small arithmetic circuits. Later, [DSY09] observed a similar result for bounded depth circuits. By combining their result with our Observation 1 we obtain the following corollary.…”
Section: Extensions Of Theorem 11supporting
confidence: 61%
“…Another line of works that is related to our results is that of Kabanets and Impagliazzo [KI04] and of [DSY09]. There it was shown that the question of derandomizing the PIT problem is closely related to the problem of proving lower bounds for arithmetic circuits (Corollary 4.7, given in Section 4, is an analogous result).…”
Section: Related Workmentioning
confidence: 79%
See 1 more Smart Citation
“…PIT is a central problem in algebraic complexity. Deterministically solving PIT is known to imply lower bounds for arithmetic circuits [HS80,Agr05,KI04,DSY09]. PIT also has some algorithmic implications.…”
Section: Every Other Gate Of C Is Labeled By Either '×' or '+' And mentioning
confidence: 99%
“…Kabanets and Impagliazzo [26] showed that, if the permanent requires large arithmetic circuits, then the probabilistic algorithm to test if two arithmetic formulae (or, more generally, two arithmetic circuits of polynomial degree) are equivalent can be simulated by a quick deterministic algorithm. Subsequently, Dvir et al [27] built on the techniques of Kabanets and Impagliazzo, to show that, if one could present a multilinear polynomial (such as the permanent) that requires depthd arithmetic formulae of size 2 n e , then the probabilistic algorithm to test if two arithmetic circuits of depth d − 5 are equivalent (where, in addition, the variables in these circuits have degree at most log O(1) n) can be derandomized to obtain a 2 log O(1) n deterministic algorithm for the problem.…”
Section: Introductionmentioning
confidence: 99%